Design Construction of Shrimp Paste Molder - Muhammad Rasyid Lubis; Ainun Rohanah; Nazif Ichwan (Universitas Sumatera Utara, 2016)
Manual molding shrimp paste was considered not attractive because the shape of the paste was not the same and reduced the price of shrimp paste. The purpose of this research was to design, build, test and analyze the economic value of shrimp paste molder. This research was conducted in by literature study, equipment tests and parameters observation. The parameters observed were effective capacity, yield and economic analysis. Based on this research, it was summarized that the effective capacity of the equipment was 51,54 kg/hour and the yield was 71,33%. Economic analysis was as follows: basic costs for the first to the fifth year was Rp.224,59/kg, Rp.225,16/kg, Rp.225,38/kg, Rp.226,45/kg, Rp.227,16/kg respectively. Break even point (BEP) was at 161,85 kg/year of shrimp paste molded. Net present value (NPV) was Rp.210.420.009. Internal rate of return (IRR) was 47,64%. Keywords: shrimp paste, molder, machine